Relationship between human resource practices and talent retention among professional and management staff of a public university in Malaysia - Supian, Siti Rozana; Ismail, Ismi Arif; Sidi, Fatimah; Omar, Zoharah (Human Resource Management Academic Research Society, 2018)
The main objective of this study is to examine the relationship between human resource practices and talent retention and at the same time determine the dominant factor that contributes to talent retention among the professional and management staff in Uni A. Descriptive and correlational methods were used as the study design and a total of 381 of professional and management staffs was selected using non-proportionate simple random sampling method. Self-administered questionnaires were distributed and 282 (74%) responses were collected. Finding of study indicates that human resource practice that consists of eight variables correlates significantly with retention. Organizational work environment was found to have the strongest correlation with retention followed by organizational leadership, and person-organization fit, and teamwork. Second, the result also confirms that there is a significant influence of human resource practice on talent retention. Apparently, work environment was found to be the dominant human resource practice in retaining talent in Uni A and it also exposes that organizational commitment model was found to be more effective to measure the influence of HRP on retention as compared to intent to stay model. Thus, from the study it can be concluded that work environment is the key human resource practices in retaining talent in Uni A followed by organizational leadership and person-organization fit. Ignoring this relationship will be a risk to talent retention in Uni A and affecting university’s function and performance. It is recommended that the university to invest money and effort as to implement a structured retention management strategy in order to retain talent focusing on work environment, leadership development and person-organization fit.